The influence of ZrO2 additive on sintering and microstructure of lithium and lithium-titanium-zinc ferrites - Lysenko E. N. Elena Nikolaevna; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Surzhikov A. P. Anatoly Petrovich; Nikolaeva S. A. Svetlana Andreevna; Vlasov V. A. Vitaliy Anatolievich (2018, 2018)
Title screen